Effects of layering technique on the shade of resin overlays and the microhardness of dual cure resin cement - Hoon-Sang Chang; Sung-Ok Hong (Sociedade Brasileira de Pesquisa Odontológica, 2014)
The purpose of this study was to assess the color of layered resin overlays and to test the early microhardness of dual cure resin cement (DCRC) light cured through the layered resin overlays. Resin overlays of 1.5 mm thickness were fabricated with the A3 shade of Z350 (Group 1L), the A3B and A3E shades of Supreme XT (Group 2L), and the A3, E3, and T1 shades of Sinfony (Group 3L) using one, two, and three layers, respectively (n = 7). Each layer of the resin overlays was set in equal thickness. The color of the resin overlays was measured with a colorimeter and compared with an A3 shade resin denture tooth. DCRC was light cured through the resin overlays, and the early microhardness of the DCRC was measured. The ΔE value between the denture tooth and the resin overlays and the Vickers hardness number (VHN) of the DCRC were analyzed with one-way ANOVA and Tukey's HSD test. The color differences were 8.9 ± 0.5, 5.3 ± 1.0, and 7.3 ± 0.5 and the VHNs were 19.4 ± 1.1, 21.1 ± 0.9, and 29.3 ± 0.6 for Groups 1L, 2L, and 3L, respectively. Therefore, to match the designated tooth color of resin inlays and to increase the early microhardness of DCRC, layered resin inlays are more appropriate than single-dentin-layer resin inlays. However, the translucent layer should be used cautiously because the color difference of resin inlays with a translucent layer was affected more than those without a translucent layer.